2014
DOI: 10.2166/wcc.2014.108
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impacts of increase in temperature on irrigation water requirements in Palakkad district: a case study in humid tropical Kerala

Abstract: Rise in temperature is one of the predicted impacts of climate change with significant implications on water resources management. An attempt has been made to calculate the water requirement of crops in different agro-ecological zones of Palakkad district in humid tropical Kerala using the CROPWAT 8.0 model. Sensitivity analysis was done for a simulated rise in temperature from 0.5 to 3.0 °C keeping other parameters the same. The analysis showed that the total crop water requirement of all the major crops, lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Effective rainfall: Effective rainfall is calculated based on rainfall data available from various stations within these AEUs, using the inbuilt formula (eqs (2) and (3)) of USDA Soil Conservation Service (SCS) in CROPWAT model. P eff (dec) = (P dec * (125 -0.6 * P dec ))/125 for…”
Section: Meteorological Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Effective rainfall: Effective rainfall is calculated based on rainfall data available from various stations within these AEUs, using the inbuilt formula (eqs (2) and (3)) of USDA Soil Conservation Service (SCS) in CROPWAT model. P eff (dec) = (P dec * (125 -0.6 * P dec ))/125 for…”
Section: Meteorological Datamentioning
confidence: 99%
“…Details such as planting season, crop duration, depth of active root zone, canopy coverage as a percentage of spacing of various crops are based on earlier studies 2,22 . Crop coefficient values (K c ) used in our study are given in Table 2.…”
Section: Meteorological Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Water supply matters in the world that will soon have to grow food for billions more people as world population is projected to peak at 9.3 billion in 2050, an increase of 28%. Analysis showed that the total crop water requirement of all major crops increased with the rising temperature thereby increasing the simulated irrigation water demand (Kijne, 2010;Surendran et al, 2014). In the future, food and livelihood security may be challenged due to global environmental changes, particularly global climatic changes that evidence has *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%